State-level public health preparedness indices as predictors of COVID-19 mortality outcomes: results from the United States of America in 2020 - Boyce, Matthew R. (Frontiers in Epidemiology, 2023)
This study evaluates associations between state-level preparedness indices and reported COVID-19-related mortality outcomes in all 50 states and the District of Columbia in the United States of America during three distinct time periods throughout the first year of the COVID-19 pandemic. State-level preparedness data for the year 2019 were gathered from the National Health Security Preparedness and Trust for America's Health Indices, and COVID-19-related mortality data for March-December 2020 (i.e., excess mortality and reported COVID-19 mortality rates) were collected in May 2022. Linear regression analyses were conducted to examine associations during three distinct time periods. Statistically significant positive associations were observed between both indices and reported COVID-19 mortality rates during the first time period. A statistically significant negative association was observed between one preparedness index and excess mortality during the second time period. No other significant associations existed for the outcomes or time periods considered in this analysis. These results demonstrate that state-level preparedness indices were not well attuned to COVID-19-related mortality outcomes during the first year of the pandemic. This suggests that current measures of state-level preparedness may be underinclusive and require a reconceptualization to improve their utility for public health practice.